KEDUDUKAN HAK ISTERI DARI PERSPEKTIF HUKUM SYARAK DAN UNDANG-UNDANG KELUARGA ISLAM DI MALAYSIA - Tapah, Suwaid (Jurnal Syariah, 2019)
In this article, the author elaborates fthe rights that women or wives deserve in a marriage according to Islam. For instances, a wife should deserve from her husband (i) a good treatment/entertainment, (ii) maintenance (nafaqah), protection, religious education as well as justice if a husband practices polygamy. In tenns of those rights, the author explains in details provisions according to Syariah as well as what is enacted and practised in Malaysia, i.e Syariah Courts as stated in Muslim Family Law of every state in The Federation. In other words, Syariah Court is a legal enforcement body if there is a negligence or abuse of their (wives) rights which affects their happiness, harmony and tranquility. However, this protection from Syariah Court would not take place unless a wife reports it first to the Syariah Court.